Use of RAAS Inhibitors and Risk of Clinical Deterioration in COVID-19: Results From an Italian Cohort of 133 Hypertensives - Felice, Carla; Nardin, Chiara; Di Tanna, Gian Luca; Grossi, Ugo; Bernardi, Enrico; Scaldaferri, Luca; Romagnoli, Micaela; Tonon, Luca; Cavasin, Paola; Novello, Simone; Scarpa, Riccardo; Farnia, Antonio; et al. (American journal of hypertension, 2020)
The effect of chronic use of renin-angiotensin-aldosterone system (RAAS) inhibitors on the severity of COVID-19 infection is still unclear in patients with hypertension. We aimed to investigate the association between chronic use of angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) and COVID-19-related outcomes in hypertensive patients.BACKGROUNDThe effect of chronic use of renin-angiotensin-aldosterone system (RAAS) inhibitors on the severity of COVID-19 infection is still unclear in patients with hypertension. We aimed to investigate the association between chronic use of angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) and COVID-19-related outcomes in hypertensive patients.A single-center study was conducted on 133 consecutive hypertensive subjects presenting to the emergency department with acute respiratory symptoms and/or fever who were diagnosed with COVID-19 infection between 9 and 31 March 2020.METHODSA single-center study was conducted on 133 consecutive hypertensive subjects presenting to the emergency department with acute respiratory symptoms and/or fever who were diagnosed with COVID-19 infection between 9 and 31 March 2020.All patients were grouped according to their chronic antihypertensive medications (ACEIs, N = 40; ARBs, N = 42; not on RAAS inhibitors, N = 51). There was no statistical difference between ACEIs and ARBs groups in terms of hospital admission rate, oxygen therapy, and need for noninvasive ventilation. Patients chronically treated with RAAS inhibitors showed a significantly lower rate of admission to semi-intensive/intensive care units, when compared with the non-RAAS population (odds ratio (OR) 0.25, confidence interval (CI) 95% 0.09-0.66, P = 0.006). Similarly, the risk of mortality was lower in the former group, although not reaching statistical significance (OR 0.56, CI 95% 0.17-1.83, P = 0.341).RESULTSAll patients were grouped according to their chronic antihypertensive medications (ACEIs, N = 40; ARBs, N = 42; not on RAAS inhibitors, N = 51). There was no statistical difference between ACEIs and ARBs groups in terms of hospital admission rate, oxygen therapy, and need for noninvasive ventilation. Patients chronically treated with RAAS inhibitors showed a significantly lower rate of admission to semi-intensive/intensive care units, when compared with the non-RAAS population (odds ratio (OR) 0.25, confidence interval (CI) 95% 0.09-0.66, P = 0.006). Similarly, the risk of mortality was lower in the former group, although not reaching statistical significance (OR 0.56, CI 95% 0.17-1.83, P = 0.341).Our data suggest that chronic use of RAAS inhibitors does not negatively affect clinical course of COVID-19 in hypertensive patients. Further studies are needed to confirm this finding and determine whether RAAS inhibitors may have a protective effect on COVID-19-related morbidity and mortality.CONCLUSIONSOur data suggest that chronic use of RAAS inhibitors does not negatively affect clinical course of COVID-19 in hypertensive patients. Further studies are needed to confirm this finding and determine whether RAAS inhibitors may have a protective effect on COVID-19-related morbidity and mortality.